1956
DOI: 10.1113/jphysiol.1956.sp005479
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Na+ depletion on the Na+:K+ ratio of the parotid saliva of the sheep

Abstract: It is well known that the continued removal of gastric juice from animals or man does not radically alter the composition of the juice (Dragstedt & Ellis, 1930; Katsch & Mellinghoff, 1933). This was found despite the loss of up to half the body chlorides (Lim & Ni, 1925-6). McCance (1938) reviewed the literature on the effect of salt deficiency on the electrolyte composition of body secretions. In his own experiments he produced depletion by a deficient diet and repeated sweats. The depletion was great enough … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
89
1

Year Published

1960
1960
1986
1986

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 8 publications
(8 reference statements)
8
89
1
Order By: Relevance
“…Denton (1957 a) showed that parotid secretion was wholly inhibited in untrained sheep when they were forcibly laid on their sides. Denton (1956) and of Coats & Wright (1957). Denton (1957b) found that the total electrolyte concentration of parotid saliva was considerably greater than that of plasma and thus regarded the saliva as being hypertonic to plasma.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Denton (1957 a) showed that parotid secretion was wholly inhibited in untrained sheep when they were forcibly laid on their sides. Denton (1956) and of Coats & Wright (1957). Denton (1957b) found that the total electrolyte concentration of parotid saliva was considerably greater than that of plasma and thus regarded the saliva as being hypertonic to plasma.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were collected under conditions of alternating rest and reflex stimulation of the parotid from the oesophagus and reticulorumen, but no stimuli were applied to the mouth. Denton (1956) and of Coats & Wright (1957). For example, parotid saliva was collected continuously for 8 days from an adult sheep, Sheep 5, that had been trained to drink saliva from a bottle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No supplementary salt was allowed during sodium depletion, but water was allowed ad libitum. Sodium depletion was induced by draining saliva from the right parotid gland (Denton, 1956;Dobson, Kay & McDonald, 1960). Data on maternal parameters were collected from both the depletion and the control ewes on the day of commencement of sodium depletion and on the day before Caesarean section.…”
Section: Methodsmentioning
confidence: 99%
“…(6) In rat and human parotid ,glands and cat submandibular glands, similar salivary electrolyte patterns have been observed after both parasympathomimetic stimulation and parasympathetic nerve or reflex stimulation of flow (Hildes and Ferguson 1955;Schneyer and Hall 1965;Mangos and Braun 1966;Petersen and Poulsen 1967;Knauf and Fr6mter 1970a;Kaladelfos and Young 1974). In sodium-deficient sheep, mineralocorticoids acton the duct system of the parotid gland causing increased reabsorption of sodium in exchange for potassium (Blair-West et al 1969;Compton and Young 1976) and under these conditions concentration of sodium in the saliva should be ap.d is positively correlated with salivary flow (Denton 1956;Beal et al 1975). For salivary sodium concentration to be negatively correlated with flow this mineralocorticoid-dependent reabsorption of sodium must be minimal and thus the Na + /K + concentration ratio of the saliva should be high.…”
mentioning
confidence: 99%